Ethnomathematics Based Exploration of Geometric Concepts in Cirebon Rattan Crafts - Wulandari, Diana Ayu; Sholihah, Fajriatus (Jurnal Sains Sosio Humaniora, 2025)
This study aims to identify and describe the mathematical concepts embedded in Cirebon’s traditional rattan crafts and to examine their potential use as contextual resources for mathematics learning. Using a qualitative method with an ethnographic approach, data were collected through direct observation of rattan craft production and semi-structured interviews with local artisans. The analysis revealed several geometric concepts present in the motifs and construction processes of rattan crafts, including reflection and translation properties in transformation geometry, rectangular forms in weaving patterns, and measurement principles applied in determining the dimensions of rattan furniture components. These findings show that cultural artefacts contain rich mathematical structures that can support contextual and meaningful learning. The novelty of this study lies in its systematic ethnomathematical exploration of rattan craftsmanship in Cirebon, an area not previously examined in existing ethnomathematics literature and in demonstrating how these cultural practices can serve as conceptual bridges for introducing abstract mathematical ideas to students. This study offers a new perspective on integrating local cultural knowledge into mathematics education, thereby strengthening the relevance of mathematics to students’ real-world experiences.